LEAD ISOTOPIC COMPOSITIONS IN THE EPICA DOME C ICE CORE AND SOUTHERN HEMISPHERE POTENTIAL SOURCE AREAS - P. VALLELONGA; A. WEGNER; C. DELMONTE; G. BURTON; F. VANHAECKE; K. J. R. ROSMAN; S. HONG; C. F. BOUTRON; GABRIELLI, PAOLO; BALLIANA, Eleonora; TURETTA, Clara; CESCON, Paolo; et al. (Quaternary Science Reviews, 2010)
A record of Pb isotopic compositions and Pb and Ba concentrations are presented for the EPICA Dome C ice core covering the past 220 ky, indicating the characteristics of dust and volcanic Pb deposition in central East Antarctica. Lead isotopic compositions are also reported in a suite of soil and loess samples from the Southern Hemisphere (Australia, Southern Africa, Southern South America, New Zealand, Antarctica) in order to evaluate the provenance of dust present in Antarctic ice. Lead isotopic compo-sitions in Dome C ice support the contention that Southern South America was an important source of dust in Antarctica during the last two glacial maxima, and furthermore suggest occasional dust contri-butions from local Antarctic sources. The isotopic signature of Pb in Antarctic ice is altered by the presence of volcanic Pb, inhibiting the evaluation of glacial–interglacial changes in dust sources and the evaluation of Australia as a source of dust to Antarctica. Consequently, an accurate evaluation of the predominant source(s) of Antarctic dust can only be obtained from glacial maxima, when dust-Pb concentrations were greatest. These data confirm that volcanic Pb is present throughout Antarctica and is emitted in a physical phase that is free from Ba, while dust Pb is transported within a matrix containing Ba and other crustal elements